2010
DOI: 10.5194/angeo-28-449-2010
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between pre-sunset electrojet strength, pre-reversal enhancement and equatorial spread-F onset

Abstract: Abstract. The virtual height of the bottom side F-region (h F ) and equatorial spread-F (ESF) onsets at Chumphon (10.7 • N, 99.4 • E; 3.3 • N magnetic latitude) were compared with the behaviour of equatorial electrojet (EEJ) ground strength at Phuket (8.1 • N, 98.3 • E; 0.1 • N magnetic latitude) during the period from November 2007 to October 2008. Increase in the F-layer height and ESF onsets during the evening hours were well connected with the EEJ ground strength before sunset, namely, both the height incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 27 publications
(45 reference statements)
3
27
1
Order By: Relevance
“…The strong eastward equatorial electric field during the pre-reversal enhancement is linked to another phenomena called equatorial spread-F or plasma bubble, which is characterized by a depletion of the equatorial ionospheric plasma density (e.g., Burke et al 2004;Stolle et al 2006). Attempts have been made by several authors (e.g., Sreeja et al 2009;Uemoto et al 2010;Hajra et al 2012) to find a link between geomagnetic daily variations and the occurrence of the equatorial spread-F. For example, Uemoto et al (2010) reported that the occurrence of the equatorial spread-F is reduced when the equatorial electrojet 1-2 hours prior to the sunset is westward. Their results suggest the possibility of the detection of the equatorial spread-F using ground magnetometer data.…”
Section: Eej Intensity and Equatorial F-region Parametersmentioning
confidence: 99%
“…The strong eastward equatorial electric field during the pre-reversal enhancement is linked to another phenomena called equatorial spread-F or plasma bubble, which is characterized by a depletion of the equatorial ionospheric plasma density (e.g., Burke et al 2004;Stolle et al 2006). Attempts have been made by several authors (e.g., Sreeja et al 2009;Uemoto et al 2010;Hajra et al 2012) to find a link between geomagnetic daily variations and the occurrence of the equatorial spread-F. For example, Uemoto et al (2010) reported that the occurrence of the equatorial spread-F is reduced when the equatorial electrojet 1-2 hours prior to the sunset is westward. Their results suggest the possibility of the detection of the equatorial spread-F using ground magnetometer data.…”
Section: Eej Intensity and Equatorial F-region Parametersmentioning
confidence: 99%
“…In addition, the daytime integrated EEJ strength values for both the hemispheres were evaluated by integrating all the hourly EEJ strengths from 07:00 to 12:00 LT. This gives the daytime integrated equatorial electrojet (IEEJ) strength values for each day (Uemoto et al, 2010;Venkatesh et al, 2015).…”
Section: Equatorial Electrojet (Eej) and Its Integrated (Ieej) Strengthmentioning
confidence: 99%
“…The transportation of plasma to higher latitudes through the EIA phenomenon is wellknown to relate with eastward electric field/EEJ and thermospheric meridional neutral wind. Older experiments from GPS measurements that unveil thermospheric meridional neutral wind effect on plasma transportation in the F region (de Paula et al, 2015) are few compared with electric field/EEJ (Venkatesh et al, 2015;Chen et al, 2008). While the electric field/EEJ is transporting the plasma across higher latitudes within low latitudes, thermospheric meridional neutral wind is modulating the transporting plasma either poleward or equatorward.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations